Discoveries and Properties of EL CVn–type Binaries in the TESS Survey - Jianping Xiong; Zhenwei Li; Jiao Li; Xiaobin Zhang; Xiaodian Chen; Kaifan Ji; Zhanwen Han; Xuefei Chen (The Astrophysical Journal)
EL CVn–type systems represent a rare evolutionary stage in binary star evolution, providing ideal laboratories for investigating stable mass-transfer processes and the formation of extremely low-mass white dwarfs (ELM WDs). The Transiting Exoplanet Survey Satellite (TESS) has delivered an extensive collection of high-precision time-domain photometric data, which is invaluable for studying EL CVn binaries. In this study, we identified 29 EL CVn systems from the TESS eclipsing binary catalogs (sectors 1–65), 11 of which are newly discovered. These systems consist of smaller, hotter prehelium WDs and A/F main-sequence stars. The orbital periods of these binaries range from 0.64 to 2.5 days. Utilizing TESS light curves, Gaia distances, and multiband photometric data (e.g., Galaxy Evolution Explorer, Two Micron All Sky Survey, Wide-field Infrared Survey Explorer, SkyMapper), we modeled the light curves and spectral energy distributions to derive system parameters, including effective temperatures, masses, and radii. These systems were then compared with the WD mass–period relation and the evolutionary tracks of ELM WDs. The comparison reveals that these binaries are consistent with the expected mass–period relation for WDs and align well with the evolutionary tracks on the T _eff − $logg$ diagram for ELM WDs. This result suggests that these EL CVn systems likely formed through stable mass-transfer processes. We provide a catalog of complete parameters for 29 EL CVn systems identified from the TESS survey. This catalog will serve as an essential resource for studying binary mass transfer, WD formation, and pulsation phenomena in EL CVn–type systems.